WHAT MOTIVATES THE CREATIVITY OF GENERATION Z EMPLOYEES? THE INFLUENCE OF EXTRINSIC AND INCRISTIC MOTIVATING FACTORS ON THE EXAMPLE OF IT SPECIALISTS FROM EU COUNTRIES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Generation Z is entering the labor market. Like the previous generation, Generation Z has its own specific characteristics, values and expectations. This creates new challenges for managers and organizers of work processes in companies. The object of this study is IT professionals belonging to generation Z. Managing of creative employees is in itself, a complex task. Combined  with the characteristics of the new generation, this task becomes especially important and difficult. Currently, there is a dearth of research in the academic literature regarding work motivation and work expectations for Generation Z, as this generation is just beginning its work life. This study seeks to clarify these issues. Empirical data for the study was collected through an online survey of Generation Z IT professionals from EU countries. The sample size is 2153 individuals. The study used intrinsic and extrinsic motivation theory and social motivation theory as the theoretical framework. The results of the study show that for IT professionals of generation Z it is primarily important to have a job where their professional skills are valued and conditions for the development of these skills are created, as well as their contribution to labor results is fairly evaluated.    For IT professionals of this generation, it is important to work among people who share their values and beliefs, to have time for personal life and the opportunity to participate in socially important projects. Their creativity is enhanced when it is necessary to do a very important job that will bring respect to the team. They are not afraid of losing their jobs and are willing to take risks.